APPLICATION OF THE CLUSTERING METHOD FOR GROUPING DATA BASED ON FAMILY SOCIO-ECONOMIC STATUS - Hidayati, Erika (Yayasan Bina Internusa Mabarindo, 2023)
Socio-economic is a position that is regulated socially and places a person in a certain position in society. Socio-economic conditions of the community can be seen through the aspects of education, employment and income. The socio-economic condition of the community can be said to be good if their daily needs have been met, be it the need for clothing, food or shelter, conversely if one of these needs is not fulfilled then it can be said that the socio-economic condition is bad. Writing this proposal uses the clustering method which is one of the data mining techniques for grouping basic family data using the k-means algorithm clustering method. By applying 20 alternative data samples of student data and providing a total of 3 clusters, and utilizing 3 main criteria as research in this proposal, the resulting number of cluster 1 is 11 data, cluster 2 is 7 data. And cluster 3 as much as 3 data. This Family Basic Data grouping system is designed with the MATLAB application programming language and utilizes the GUI as its interface.